Stan wojny, stan wojenny i stan wyjątkowy w konstytucjach europejskich państw socjalistycznych - Smoliński, Tadeusz (Wydział Prawa i Administracji UAM, 1982)
Constitutions of the European socialist states provide a possibility of proclaiming a state of war and a state of martial law (the latter is hereinafter called the "warlike state" to render the lexical similarity of the discussed concepts in Polish). The state of war is a notion of international law, while the "warlike state" is a notion of State (internal) law and it is not necessarily related to the actual threat of a possible international conflict. The "warlike state" is essentially an equivalent of the state of emergency defined in non-Marxist constitutions. The socialist constitutions (except of the Bulgarian one) do not use the notion of the state of emergency, for a certainty not to arise any unpleasant reflections associated with the introduction of the state of emergency in some non-Marxist states. The term of "warlike state" was adopted from the Soviet constitution to many other constitutions of the European socialist states. The state of war can be proclaimed by parliaments and by supreme presidential organs in the periods between the sessions of parliaments. It can be introduced in two cases: 1) in case of agression against a European socialist state, 2) if the necessity of common defence against an agression is consequent upon the international agreements. The "warlike state" (state of emergency) can be proclaimed by the supreme presidential organ or by the president (in Romania). By virtue of constitutional premises it is introduced with the aim of ensuring the interests of defence, security of State and public order. It follows explicitely or it can be interpreted from the constitutional provisions that the "warlike state" can be introduced with the aim of protecting the socialist system. Neither the state of war, nor the "warlike state" proclaimed by the supreme presidential organ have to be subsequently approved by the parliament. Regulation of the state of war and of the "warlike state" in the discussed state constitutions are very laconic (similarly as literature on that matter in the discussed countries). To a large extent it is resulting from the fact that the "warlike state" has never before been proclaimed in the European socialist countries and it was not assumed that the aggravation of the internal situation would result in the introduction of the "warlike state" (state of emergency) after many years of the construction of socialism. The constitutions under discussion also endowed the governments with a capacity of undertaking certain actions (without proclaiming the "warlike state") in order to protect security and public order. And it was precisely that competence which has been exercised so far by the governments of the European socialist states whenever a necessity of establishing order arised. The introduction of the "warlike state" in Poland will probably stimulate the future enactment of the detailed laws regulating the situation in a State under a "warlike state".
State of War, State of Martial Law and State of Emergency in Constitutions of the European Socialist States